The hybrid model of ChatGPT and other AI technologies for automatic Short-Video creation in Vietnam - Pham, Cao Văn; Pham, Hồng Nhung; Vo, Trọng Cang (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
Nowadays, the innovation of artificial intelligence (AI) has created numerous opportunities for advancement in a variety of fields. At the end of 2022, OpenAI company launched a new ChatBot product called ChatPGT, which has created a big trend not only in Vietnam but also around the world, because it has many prominent features. Furthermore, in recent years, Short-Video has become a big trend on Vietnam’s most popular social networking platforms, including Youtube, Tiktok, and Facebook. By researching and combining the features of ChatGPT and a number of artificial intelligence tool platforms available in Vietnam, the study proposes an application model of ChatGPT and AI to create short videos with a quick build time and with high quality such as auto scripting, text-to-image, text-to-video, text-to-speech, text-to-speaker. Content creators on social networking platforms can use this model to make the process of creating Short-Video more efficient.